Modernization of agriculture in Kharkiv province (as an example, L. E. Kenig’s latifundiya 1874-1903) - Лисенко, Майя (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2016)
This paper examines the modernization of the agrarian sector of the Kharkiv province, as an example L. E. Kenig’s estates. This article describes creation, the certain types of a new type of enterprise. These savings were a rarity in the Ukrainian provinces. L. E. Kenig’s latifundiya was efficiently organized. By their nature agriculture was diversified. The central place occupied by sugar refining and winemaking. Much attention was given to livestock, field work, forestry work. It was built on the basis of agronomy in this techno-agricultural enterprise. Enterprises of latifundiya had the latest equipment at that time. Research conducted on the breeding station. The owner of the estates has worked with companies of agriculture and agricultural industry. Exhibits made in latifundiya, shown at agricultural exhibitions. The estates were created good working conditions for employees and workers. L. E. Kenig engaged in charity, which emphasized not only the enterprise, but also the nature of his public activities. The creation of such farms indicated the modernization of the agrarian sector in Kharkiv region and changes in society .